SAT0340 Infliximab Levels and Anti-Infliximab Antibodies Comparison between Two Comercial ELISA Versions in Patients with Ankylosing Spondylitis. (10th June 2014) - Hernández Flόrez, D.; Valor, L.; Nieto, J.C.; Martinez, L.; de la Torre, I.; del Río, T.; Gonzalez, C.; Lopez-Longo, J.; Monteagudo, I.; Naredo, E.; Montoro, M.; Carreño Perez, L.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory disease which can result in invalidating deformities of the joints and spine at an early age. The introduction of tumor necrosis factor (TNF) blocking agents has changed the treatment options in AS. Nevertheless, the reasons for lack or loss of response to infliximab (IFX) are unclear. So far determinations of both, IFX serum levels and the presence of anti-drug antibodies (ADA) anti-IFX have not been standardized for clinical use. Objectives: To assess the correlation between two available versions (V.1 and V.2) of a commercial enzyme-linked immunosorbent assay (ELISA) for serum levels of IFX and IFX-ADA in patients with AS. Methods: In this cross sectional study we assessed 40 serum samples taken prior to infusion from patients diagnosed with AS treated with IFX for more than 12 months (1st line of biological treatment). IFX levels and IFX-ADA were measured using two different ELISA assays [Promonitor® IFX R1 and R2 (V.1), Promonitor® IFX and Anti-IFX (V.2) (Progenika Biopharma, Spain)] according to manufacturer's specifications. The relation comparing V.1 and V.2 for IFX levels and IFX-ADA concentrations was performed using the coefficient of variation (CV), the Cohen's Kappa coefficient, the Pearson's r, the intraclass correlation coefficient (ICC) and the Lin's concordance correlation coefficient (CCC). Bland-Altman plots were drawn to compare both versions of the assays. Results: As shown in the table below, we found a greater CV for IFX levels than for IFX-ADA. Regarding the qualitative results the Cohen's Kappa was from moderate to fair and considering the quantitative results the Pearson's r was low for IFX levels and high for IFX-ADA, the ICC was questionable for both versions and both determinations. We also determined the CCC and the results showed a poor agreement. Bland-Altman plots showed the difference between both versions for IFX levels (Fig. 1 ). Conclusions: A low reliability for IFX levels and IFX-ADA was obtained for both versions. There is a need to standardize laboratory techniques (variability inter/intra-assay and inter/intra-laboratory) in order to validate this information and its possible clinical application. Disclosure of Interest: D. Hernández Flόrez: None declared, L. Valor: None declared, J. C. Nieto: None declared, L. Martinez: None declared, I. de la Torre: None declared, T. del Río: None declared, C. Gonzalez: None declared, J. Lopez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, M. Montoro: None declared, L. Carreño Perez: None declared DOI: 10.1136/annrheumdis-2014-eular.3274